Access to 1,2-Dihydroisoquinolines through Gold-Catalyzed Formal [4+2] Cycloaddition - Xin, Zhuo; Kramer, Søren; Overgaard, Jacob; Skrydstrup, Troels (Chemistry : a European journal, 2014)
A new synthetic route to the privileged 1,2‐dihydroisoquinolines is reported. This method, which relies on a gold‐catalyzed formal [4+2] cycloaddition between ynamides and imines, provides a new retrosynthetic disconnection of the 1,2‐dihydroisoquinoline core by installing the 1,8a CC and 2,3 CN bonds in one step. Both aldimines and ketimines can be used as substrates. In addition, one example of dihydrofuropyridine synthesis is also demonstrated. Heterocycles: A new synthetic route to the privileged 1,2‐dihydroisoquinolines is reported. This method, which relies on a gold‐catalyzed formal [4+2] cycloaddition between ynamides and imines, provides a new retrosynthetic disconnection of the 1,2‐dihydroisoquinoline core by installing the 1,8a CC and 2,3 CN bonds in one step. Both aldimines and ketimines can be used as substrates. In addition, one example of dihydrofuropyridine synthesis is also demonstrated (see scheme).